CGIAR Climate change West Africa Program informs the adoption of a public-private partnership business model for climate information services in Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Based on previous success stories from collaboration with CGIAR Program on climate change, agriculture & Food Security, Esoko, a private Information & Communication Technology (ICT) company, has taken up a Public-Private Partnership (PPP) business model proposed by CCAFS to allow sustainable and equitable dissemination of Climate Information Services. The PPP pilot which commenced in April 2018 now has 274,321 beneficiaries who have agreed to pay US$0.20 a month to receive timely market alerts and climate information on their mobile phones.